Attitudes and Behaviors toward traditional music among Chinese students: the role of individual, family, and school factors - Jin Liu; Tian Li (PLoS ONE, 2026)
Background Traditional music is vital for cultural identity, particularly among youth in China, yet factors influencing students’ engagement with it remain underexplored. Purpose This study investigates the key factors affecting primary and secondary school students’ attitudes and behaviors toward traditional music in Guangdong Province, focusing on gender, grade level, parental support, and regional disparities. Methods Utilizing a mixed-methods design, the research involved surveys and interviews with students, parents, and educators to gather comprehensive insights. Major Findings The study revealed significant gender differences: female students displayed more positive attitudes and higher participation. Younger students exhibited greater enthusiasm, which declines with academic pressure. Parental involvement was identified as crucial, but the unexpected negative impact of parental artistic ability suggests more nuanced dynamics. Implications These findings highlight the need for tailored music education policies that are inclusive and responsive to diverse student backgrounds, particularly in less developed regions. Conclusion By understanding the multifaceted influences on students’ engagement, this study underscores the importance of fostering youth involvement in traditional music as a means of cultural preservation in an evolving educational landscape.